Crystal structure of diaqua-bis(μ2-2-carboxy-3,4,5,6-tetrafluorobenzoato-κ2O:O′)-bis(phenanthroline-κ2N,N′)-bis(μ2-3,4,5,6-tetrafluorophthalato-κ3O:O,O′)dieuropium(III) – phenanthroline (1/2), C40H19EuF8N4O9 - Zhang Xiao-Yu; Liu Xin-Fang; Zhao Bei-Bei; Huang Shi-Jie (Zeitschrift für Kristallographie - New Crystal Structures)
C40H19EuF8N4O9, triclinic, P1‾$P\overline{1}$ (no. 2), a = 11.3326(4) Å, b = 12.7652(4) Å, c = 13.2629(4) Å, α = 102.266(2)°, β = 97.689(2)°, γ = 105.630(3)°, V = 1767.93(10) Å3, Z = 2, Rgt(F) = 0.0329, wRref(F2) = 0.0648, T = 293(2) K.